2009
DOI: 10.1210/jc.2008-1538
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years of Growth Hormone (GH) Replacement Normalizes Muscle Strength in GH-Deficient Adults

Abstract: Ten years of GH replacement therapy increased muscle strength during the first half of the study and thereafter partly protected against the normal age-related decline in muscle strength and neuromuscular function, resulting in approximately normalized muscle strength after 10 yr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 34 publications
4
61
0
1
Order By: Relevance
“…This is consistent with the lipolytic and anabolic effects of GH observed in previous studies (4,10,23,24), demonstrating that a moderate dose of GH can induce a sustained improvement in body composition in elderly GHD adults. GH replacement, as previously shown (10,25), had a more marked effect on isometric knee flexor strength than on isokinetic knee flexor strength, possibly as a consequence of more reduced isometric strength in untreated GHD adults (9,26). This allows to assume that increased muscle strength during GH replacement is not only due to increased muscle mass (27)(28)(29).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is consistent with the lipolytic and anabolic effects of GH observed in previous studies (4,10,23,24), demonstrating that a moderate dose of GH can induce a sustained improvement in body composition in elderly GHD adults. GH replacement, as previously shown (10,25), had a more marked effect on isometric knee flexor strength than on isokinetic knee flexor strength, possibly as a consequence of more reduced isometric strength in untreated GHD adults (9,26). This allows to assume that increased muscle strength during GH replacement is not only due to increased muscle mass (27)(28)(29).…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study, we observed a more marked response in muscle performance following the 10-year GH replacement in patients below 50 years of age compared to patients older than 50 years (10). In the present study, we therefore investigated whether the 10-year GH replacement could affect muscle strength in elderly adults with GHD above 60 years of age.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Growth hormone (GH) therapy has yielded favorable results for childhood growth disorders and adult growth hormone deficiency (GHD) [1,2]. However, the potential for the application of GH recombinant products in patients with growth hormone deficiency (GHD) is limited by the high cost, attendant risks, and inconvenience of the necessary exogenous s.c. injections.…”
Section: Introductionmentioning
confidence: 99%